2009
DOI: 10.1002/chin.200929034
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Gold(I) Complexes of KITPHOS Monophosphines: Efficient Cycloisomerization Catalysts

Abstract: Ring closure reactions O 0130Gold (I) Complexes of KITPHOS Monophosphines: Efficient Cycloisomerization Catalysts -[all yields determined by NMR]. -(HASHMI*, A. S. K.; LOOS, A.; LITTMANN, A.; BRAUN, I.; KNIGHT, J.; DOHERTY, S.; ROMINGER, F.; Adv.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…In this regard, we have recently extended this cycloaddition methodology to the Diels-Alder reaction between 1-alkynylphosphine oxides and anthracene to afford the electron-rich biaryl-like KITPHOS class of monophosphines 50-52 -architectural analogs of Buchwald's biaryl-like monophosphines [53][54][55][56] . Preliminary studies have shown that these monophosphines are highly efficient ligands that either rival or outperform their biaryl-based counterparts in palladium-catalyzed Suzuki-Miyaura and Buchwald-Hartwig cross-couplings 50,51 , a host of gold(I)-catalyzed intramolecular cycloisomerizations [57][58][59] , as well as in the ruthenium-catalyzed direct ortho arylation of 2-phenylpyridine and N-phenylpyrazole with aryl chlorides 60 . In addition, biaryl monophosphines have also been prepared by rhodium-catalyzed [2 + 2 + 2] cycloaddition [61][62][63] and Diels-Alder cycloaddition extrusion 64 .…”
Section: Simon Doherty and Catherine H Smythmentioning
confidence: 99%
“…In this regard, we have recently extended this cycloaddition methodology to the Diels-Alder reaction between 1-alkynylphosphine oxides and anthracene to afford the electron-rich biaryl-like KITPHOS class of monophosphines 50-52 -architectural analogs of Buchwald's biaryl-like monophosphines [53][54][55][56] . Preliminary studies have shown that these monophosphines are highly efficient ligands that either rival or outperform their biaryl-based counterparts in palladium-catalyzed Suzuki-Miyaura and Buchwald-Hartwig cross-couplings 50,51 , a host of gold(I)-catalyzed intramolecular cycloisomerizations [57][58][59] , as well as in the ruthenium-catalyzed direct ortho arylation of 2-phenylpyridine and N-phenylpyrazole with aryl chlorides 60 . In addition, biaryl monophosphines have also been prepared by rhodium-catalyzed [2 + 2 + 2] cycloaddition [61][62][63] and Diels-Alder cycloaddition extrusion 64 .…”
Section: Simon Doherty and Catherine H Smythmentioning
confidence: 99%